A Review Of Energy Absorption Of Automotive Bumper Beam - Su, Muhammad Nasiruddin; Arep @ Ariff, Hambali; Jaafar, Roshidah; Widodo, Wahyono Sapto; Ahmad, Mohd Nazri (Research India Publications, 2017)
Energy absorption during an impact is very important in automotive bumper system. Bumper beam is one of the main parts in bumper system which is used as protection for passengers and frontal compartment of a car during impact. This paper is carried out in order to determine the factors that affecting energy absorption of automotive composite bumper beam. Studies related to the factors affecting and optimization of bumper beam was reviewed and summarized from year 1995 to 2015. From literatures, the use of natural fiber polymer based composite have been utilized in automotive components but still in studies in bumper beam structure. A further study to use natural fiber polymer based composite in bumper beam structures need to be study.